1997
DOI: 10.1007/bf01709477
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of fosfomycin combined with ceftazidime, imipenem, amikacin, and ciprofloxacin againstPseudomonas aeruginosa

Abstract: The in vitro activity of fosfomycin in combination with ceftazidime, imipenem, amikacin, or ciprofloxacin was studied by an agar plate checkerboard method against 40 clinical isolates of Pseudomonas aeruginosa with various antibiotic resistance profiles. Fosfomycin/ciprofloxacin appeared to be the most effective combination (synergy 15%, addition 80%, indifference 5%), followed by fosfomycin/amikacin (synergy 7.5%, addition 52.5%, indifference 40%), fosfomycin/imipenem (addition 37%, indifference 63%), and fos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 8 publications
1
33
0
Order By: Relevance
“…Prolonged therapy courses also lead to the selection of hypermutator strains that, indirectly, favor the acquisition of resistance (31,32). Therefore, the treatment of multidrugresistant P. aeruginosa infections requires the combination of various antimicrobial agents (7,29,42,44). Most antibiotic resistance mechanisms in cystic fibrosis isolates of P. aeruginosa are based on mutation (31); therefore, it is expected that Fos resistance follows the same principle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prolonged therapy courses also lead to the selection of hypermutator strains that, indirectly, favor the acquisition of resistance (31,32). Therefore, the treatment of multidrugresistant P. aeruginosa infections requires the combination of various antimicrobial agents (7,29,42,44). Most antibiotic resistance mechanisms in cystic fibrosis isolates of P. aeruginosa are based on mutation (31); therefore, it is expected that Fos resistance follows the same principle.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the treatment of multidrug-resistant P. aeruginosa requires the combination of various antimicrobial agents. Fosfomycin (Fos) has been reported to be effective in combination with other antipseudomonal agents (6,29,42,44). The proportion of Fos-resistant (Fos-R) strains in clinical isolates of P. aeruginosa currently is not well known, and even the mechanisms that support Fos resistance in P. aeruginosa are not clear.…”
mentioning
confidence: 99%
“…Because our current knowledge of the pharmacodynamics of fosfomycin is so limited, responses to fosfomycin in vivo could be different from those predicted by current interpretive criteria. Responses could also vary by tissue and through synergism with other frequently coadministered antimicrobial agents (28,31,32,38). While fosfomycin is an alternative treatment choice for infections caused by multidrug-resistant pathogens, combination therapy is usually recommended when the fosfomycin MIC values are higher and because there is a tendency for resistance to develop during treatment with fosfomycin alone (15).…”
Section: Vol 55 2011mentioning
confidence: 99%
“…However, several reports have demonstrated that due to various dwell times and higher dialysate treatment volumes during cycler therapy, peritoneal clearance of antibiotics differs between CAPD and APD (1,2,6,7). Fosfomycin is a bactericidal broad-spectrum antibiotic with high in vitro activity against most common isolates of peritoneal dialysis-associated peritonitis and may be of great interest for the treatment of PD patients (3,11). Pharmacokinetics (PK) of fosfomycin in CAPD patients receiving both intravenous (i.v.)…”
mentioning
confidence: 99%